TERAPI RELAKSASI BENSON BERPENGARUH TERHADAP TEKANAN DARAH PASIEN HIPERTENSI INTRADIALITIK DI RS PANTI WILASA Dr. CIPTO SEMARANG (STIKES Telogorejo Semarang, 2022)
Management of CKD patients is divided into three, namely conservative therapy, kidney replacement therapy with hemodialysis and kidney transplant surgery therapy. Complications or complications can occur during the hemodialysis process called intradialytic complications, including intradialytic hypertension. One of the independent nursing interventions for hemodialysis nurses that can be given is Benson relaxation therapy. This study aims to determine the effect of Benson's relaxation therapy on the blood pressure of patients with intradialytic hypertension at Panti Wilasa Dr. Cipto Hospital Semarang. The research design used a quasi-experimental design with a non-equivalent control group design model. The number of samples in this study were 30 respondents which were divided into 15 respondents in the intervention group and 15 respondents in the control group. The sampling technique used was purposive sampling. The results of the Independent T-Test test obtained a value for systolic pressure p value = 0.000 (p value <0.05) and a value for diastolic pressure p value = 0.006 (p value <0.05). The conclusion of this study is that there is an effect of Benson relaxation therapy on the blood pressure of patients with intradialytic hypertension at Panti Wilasa Dr. Cipto Hospital Semarang. Recommendations from this study are independent nursing interventions for intradialytic hypertension with non-pharmacological therapy, one of which is Benson relaxation therapy. For the next researcher, the control group can be given other non-pharmacological therapies, so that they can compare the effectiveness of the two non-pharmacological therapies